2021
DOI: 10.1093/ajcn/nqaa438
|View full text |Cite
|
Sign up to set email alerts
|

Prior undernutrition and insulin production several years later in Tanzanian adults

Abstract: Background The prevalence, pathology, and existence of malnutrition-associated diabetes remain uncertain, especially with respect to adult-acquired undernutrition. Objective The aim was to investigate the association of prior undernutrition (low BMI, in kg/m2), acquired in adulthood and insulin during an oral glucose tolerance test (OGTT). Methods We followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The developmental origins of health and disease (DOHaD) concept emphasises the direct influence of chronic infections and undernutrition on structural development and physiologic function of most critical body organs during the early stages of life and development, hence increasing the future risk of metabolic conditions like type 2 diabetes (31). Undernutrition and chronic infections remain common in SSA and could explain the high rates of pancreatic beta-cell dysfunction and insulin deficiency noted in adult African patients with type 2 diabetes (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The developmental origins of health and disease (DOHaD) concept emphasises the direct influence of chronic infections and undernutrition on structural development and physiologic function of most critical body organs during the early stages of life and development, hence increasing the future risk of metabolic conditions like type 2 diabetes (31). Undernutrition and chronic infections remain common in SSA and could explain the high rates of pancreatic beta-cell dysfunction and insulin deficiency noted in adult African patients with type 2 diabetes (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…6 There are heterogeneous reports of atypical diabetes in LMICs, describing an entity of malnutrition-related, insulin-deficient diabetes related to pancreatic damage, for example, a phenotype termed fibrocalculous pancreatic diabetes, 7 but these studies often report highly selected patients, which can provide mechanistic but not epidemiologic information, 8 or precede the availability of modern assessment methods. 9 Our own work has shown that prior malnutrition in Tanzanian adults is associated with lower insulin production in men 10 and that insulin deficiency is a more common cause of diabetes than insulin resistance. 11 If malnutrition is associated with an atypical form of diabetes, driven by insulin deficiency and not resistance, then this has major implications for health policy, planning, investigation and treatment of diabetes in LMICs, because current first-line treatments of diabetes in these settings usually use treatments such as metformin which would be inappropriate for insulin-deficient diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, the increasing diabetes burden is partly driven by insulin resistance from overweight particularly seen in urban settings, associated with intake of high-calorie low-fibre diets, low levels of physical activity ( 3 , 4 ), and from infections like HIV ( 5 , 6 ). However, reduced insulin secretion due to under nutrition could also contribute to diabetes ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%